CORPORATE SOCIAL RESPONSIBILITY AND HUMAN RESOURCES MANAGEMENT: THE PUBLIC COMPANY WORKERS’ VIEW - Napoleão, Raquel; Neto, Antônio Moreira de Carvalho; Lima, Gustavo Simão; Gonçalves, Pedro; Almeida, Tatiana (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
This article examines the perception of employees and managers regarding policies and practices of Human Resources Management (HR) to promote Corporate Social Responsibility (CSR). The research was on a public company regarding to CSR Ethos Institute indicators. The research is descriptive and quantitative. The method used was the survey. Data were collected from closed questionnaires answered by the employees and managers as well as by official documents. The sample is composed of 247 employees out of a population of 850 people. The results suggest a more positive perception about the HR practices related to the indicators that deals with health, safety and working conditions care; company behavior in relation to layoffs and preparing for retirement. On the other hand, there is a less positive perception related to participative management and the relationship with contracted out workforce.